Optimization Of The Existing Government Credit Card (Kkp) Process In The Salary-Based Loan & Credit Department Of BRI: Analysis And Recommendations For Time Efficiency - Muhammad Akmal Alba; Al Hasin (International Journal of Economics, Business and Innovation Research, 2025)
This study aims to analyze and optimize the termination process of the Government Credit Card (Kartu Kredit Pemerintah/KKP) at the Salary Based Loan (SBL) Department of Bank Rakyat Indonesia (BRI). The research was motivated by existing administrative challenges, such as prolonged document waiting times and the absence of effective monitoring systems, which resulted in inefficiencies. The methods applied were process mapping and process flow analysis, which were used to visualize workflows, identify bottlenecks, and measure time efficiency. The findings reveal that the existing process required 10,203 minutes (±7 working days) with 16 activities, while the proposed process only required 1,867 minutes (±1 working day) with 10 activities. This reflects a time efficiency improvement of 81.7%, equivalent to saving more than six working days. Strategic changes proposed include workflow simplification, the introduction of a document register system, strengthened inter-unit coordination, and the implementation of a Service Level Agreement (SLA) at each process stage. The redesigned process is expected to provide faster, more transparent, and accountable services, enhance stakeholder satisfaction, and support the objectives of the KKP policy in achieving efficient state budget management.